Divergent Responses of Community Reproductive and Vegetative Phenology to Warming and Cooling: Asymmetry Versus Symmetry - Meng, Fandong; Zhang, Lirong; Niu, Haishan; Suonan, Ji; Zhang, Zhenhua; Wang, Qi; Li, Bowen; Lv, Wangwang; Wang, Shiping; Duan, Jichuang; Liu, Peipei; Renzeng, Wangmu; et al. (Frontiers in Plant Science, 2019)
Few studies have focused on the response of plant community phenology to temperature change using manipulative experiments. A lack of understanding of whether responses of community reproductive and vegetative phenological sequences to warming and cooling are asymmetrical or symmetrical limits our capacity to predict responses under warming and cooling. A reciprocal transplant experiment was conducted for 3 years to evaluate response patterns of the temperature sensitivities of community phenological sequences to warming (transferred downward) and cooling (transferred upward) along four elevations on the Tibetan Plateau. We found that the temperature sensitivities of flowering stages had asymmetric responses to warming and cooling, whereas symmetric responses to warming and cooling were observed for the vegetative phenological sequences. Our findings show that coverage changes of flowering functional groups (FFGs, i.e., early-spring flowering functional group, mid-summer flowering functional group and late-autumn flowering functional group), and their compensation effects combined with required accumulated soil temperature (RCST) to co-determine the asymmetric and symmetric responses of community phenological sequences to warming and cooling. These results suggest that coverage change in FFGs on warming and cooling processes can be a primary driver of community phenological variation, may be leading to inaccurate estimation of large scale phenology based on such as remote sensing method.